Turbulent Effect on the Dynamic Response Coefficients of Finite Journal Bearings Lubricated with Micropolar Fluid. (2016) - Das, Subrata; Guha, Sisir Kumar
Abstract: The aim of the present work is to analyse theoretically the dynamic response coefficients of fluid film of finite hydrodynamic journal bearing with micropolar lubrication in turbulent regime. The governing non-dimensional Reynolds equations for steady state and dynamic film pressures have been solved numerically to obtain the film pressure distributions which are used to determine the dynamic response coefficients in terms of stiffness and damping coefficients of fluid film. These response coefficients are used to obtain the linear stability characteristics in terms of critical mass parameter and whirl ratio. It is found that the stiffness and damping coefficients both increases with increase in Reynolds number. It is also observed that the turbulence of the micropolar lubrication has an adverse effect on stability and the whirl ratio.